Impacts of Reduced Nitrate Supply on Nitrogen Metabolism, Photosynthetic Light-Use Efficiency, and Nutritional Values of Edible Mesembryanthemum crystallinum - Jie He; Lin Qin (Frontiers in Plant Science, 2021)
Mesembryanthemum crystallinum (common ice plant), as a nutritious ready-to-eat salad in Singapore, has become popular in recent years. However, basic data about the impacts of NO3– supply on its NO3– accumulation and nutritional quality are lacking. In this study, all plants were first grown indoor hydroponically in 10% artificial seawater (ASW) with modified full-strength Netherlands Standard Composition nutrient solution for 11 days, before transferring them to different reduced NO3– solutions. All plants grew well and healthy after 7 days of treatment. However, plants grown with 3/4 N and 1/2 N were bigger with higher shoot and root fresh weight (FW), greater leaf number, and total leaf area (TLA) than those grown with full nitrogen (N), 1/4 N, and 0 N. Mesembryanthemum crystallinum grown with full N, 3/4 N, and 1/4 N had similar specific leaf area (SLA), while 0 N plants had significantly lower SLA. All plants had similar leaf succulence (LS). However, leaf water content (LWC) was lower, while leaf dry matter accumulation (LDMC) was higher in 0 N plants after 7 days of treatment. Compared with plants grown with full N, shoot NO3– concentrations in 3/4 N, 1/2 N, and 1/4 N plants were constant or slightly increased during the treatments. For 0 N plants, shoot NO3– concentration decreased significantly during the treatment compared with other plants. Shoot NO3– accumulation was associated with nitrate reductase activity (NRA). For instance, after 7 days of treatment, shoot NO3– concentration and NRA on a FW basis in 0 N plants were, respectively, 45 and 31% of full N plants. After transferring full N to 0 N for 7 days, all M. crystallinum had higher chlorophyll (Chl) content coupled with higher electron transport rate (ETR) and higher effective quantum yield of PSII, while full N plants had higher non-photochemical quenching (NPQ). The 0N plants had much higher concentrations of proline, total soluble sugar (TSS), and total ascorbic acid (ASC) than other plants. In conclusion, totally withdrawing NO3– from the growth media prior to harvest could be one of the strategies to reduce shoot NO3– concentration. Reduced NO3– supply further enhanced nutritional values as concentrations of proline, TSS, and ASC were enhanced markedly in M. crystallinum plants after transferring them from full N to 0 N.